Film Review - Train: Kyiv-War (2020) - Andrii Smytsniuk (Slovo, 2022)
Korniy Hrytsiuk's documentary “Train: Kyiv - War” attempts to rethink the War in Donbas through a journey. The train Kyiv-Kostiantynivka goes from the heart of Ukraine to its far Eastern city Kostiantynivka that is located next to the frontline. Hrytsiuk, a native of the embattled territory, interviews his fellow passengers, recording their reflections about Ukraine, Russia, the war, and the future of Donbas.
Keywords: War; Ukraine; Russia; Donbas